Redox‐Active Polymer Integrated with MXene for Ultra‐Stable and Fast Aqueous Proton Storage. (26th October 2022) - Shi, Minjie; Wang, Renyuan; Li, Lingyun; Chen, Nianting; Xiao, Peng; Yan, Chao; Yan, Xingbin
Abstract: Proton is a charge carrier with the smallest ionic size and quickest kinetics, making aqueous proton batteries (APBs), a promising technology for safe and profitable energy storage systems. Despite being potential electrode materials, organic compounds have not yet been fully investigated in terms of proton storage properties and APB applications due to their low capacity and unstable cycle life in aqueous electrolytes. Herein, a novel redox‐active polymer (PDPZ) with diquinoxalino‐phenazine as the structural unit has been designed, which is further integrated with MXene nanosheets to construct a flexible PDPZ@MXene electrode material with a rapid and ultra‐stable proton storage behavior. In‐operando monitoring techniques, i.e., in situ Raman and in situ FTIR, demonstrate the highly reversible redox reaction between CN and CN/NH bonds in electro‐active PDPZ molecule with the strong proton absorption ability. Theoretical calculation further proves the electron transfer from MXene to PDPZ promotes the redox reaction of the PDPZ@MXene electrode. As a result, a flexible APB device is developed with a considerable energy density (64.3 mWh cm −3 ), a supercapacitor‐level power density (6000 mW cm −3 ), and a record lifespan with ≈98.2% capacity retention over 10 000 cycles, revealing its potential applications in satisfying the various requirements of energy storage systems. Abstract : A redox‐active polymer‐based flexible electrode with excellent proton coordination ability is developed, which exhibits rapid, ultra‐stable, and efficient proton redox charge‐storage characteristics as evidenced by in‐operando monitoring techniques and theoretical calculations. For real applications, a metal‐free, quasi‐solid, and flexible aqueous proton battery is effectively fabricated with high energy/power densities and a record long lifespan over 10 000 cycles.